Young Australians are out for control: reconciling flexibility, security, and the next generation of labour. (2nd January 2022) - Sullivan, Rick; Goods, Caleb; Smith, Brett
ABSTRACT: Debates over workplace flexibility and security sit at the heart of ongoing tensions between industrial relation actors in Australia. The deployment of organisational strategies focused on labour market flexibility have been accompanied by ambiguous discussions and a steady rise in insecure work arrangements within advanced capitalist economies. This rising insecurity is not evenly distributed throughout the labour market, with young workers and those poised to enter the labour market facing a more volatile and precarious employment context. This article seeks to explore how young Australians transitioning into the workforce decide what forms of flexibility and security are important for them. Using qualitative methods, the research surveyed university students to explore and describe how young people consider and prioritise different aspects of the flexibility–security relationship. The findings challenge popular assumptions of the flexibility–security relationship, with respondents indicating that flexibility and security are mutually dependent enablers of employee control instead of being diametrically opposed or distinct constructs under the employee perspective. The implications of these findings pose new challenges for managers and employment relations to enable young Australians to successfully transition from school to their professional lives post-pandemic.